PS02.120: NEOADJUVANT CHEMOTHERAPY VERSUS NEOADJUVANT CHEMORADIOTHERAPY FOR CANCER OF THE OESOPHAGUS OR GASTRO-OESOPHAGEAL JUNCTION: LONG-TERM RESULTS. (14th September 2018) - Von Döbeln, Gabriella; Klevebro, Fredrik; Jacobsen, Anne-Birgitte; Hilmer Nielsen, Niels; Johnsen, Gjermund; Hatlevoll, Ingunn; Idar Glenjen, Nils; Friesland, Signe; Lundell, Lars; Nilsson, Magnus
Abstract: Background: NeoRes I is a randomized phase II trial comparing neoadjuvant chemoradiotherapy with neoadjuvant chemotherapy in the treatment of resectable oesophageal cancer. Methods: Patients with biopsy-proven adenocarcinoma or squamous cell carcinoma in the oesophagus or gastro-oesophageal junction (Siewert type I and II), T1N1 or T2–3N0–1 and M0-M1a (AJCC 6 th edition) were randomized to receive three 3-weekly cycles of cisplatin 100 mg/m 2 day 1 and fluorouracil 750 mg/m 2 /24 hours, days 1–5 with or without the addition of concurrent radiotherapy 40 Gy, 2 Gy/fraction, 5 days a week, followed by oesophageal resection with two-field lymphadenectomy. Primary endpoint was complete histopathological response rate. Survival and recurrence patterns were evaluated as secondary endpoints. Results: Between 2008 and 2013, 181 patients were enrolled in 10 participating institutions in Sweden and Norway. Patients were well matched for pre-treatment characteristics T3: 64, 1%, T2: 34, 8%, T1: 1, 1%. Adenocarcinoma: 72, 4%, squamous cell carcinoma: 27, 6%. Proximal/middle: 16, 6%, distal: 65, 2%, cardia (Siewert type II): 18, 2%. < 60 years: 36, 5%, 60–75 years: 63, 5%. Treatment-related complications have previously been described with no significant differences between the treatment groups although postoperative complications were more severe in the chemoradiotherapy group. At the time of this analysis, median follow-up time for living patients was 63 months. Overall 5-year survival was better among those who achieved complete histopathological response (74, 9%, 95% CI 54, 2–87, 2% versus 39, 3%, 95% CI 30, 6–47, 8%, P  = 0002). Despite the previously reported higher rate of tumour tissue response in those who received neoadjuvant chemoradiotherapy, this was not translated into better survival. Five-year progression-free survival was 38, 6%, 95% CI 28, 4–48, 6% (chemoradiotherapy) versus 32, 4%, 95% CI 22, 9–42, 4% (chemotherapy), P  = 0, 48. Five-year overall survival was 41, 2%, 95% CI 30, 9–51, 3% (chemoradiotherapy) versus 38, 9%, 95% CI 28, 7- 49, 0% (chemotherapy), P  = 0, 95. There were no differences in recurrence patterns between the two treatment-groups. Conclusion: This is to our knowledge the largest completed randomized trial comparing neoadjuvant chemotherapy with neoadjuvant chemoradiotherapy followed be oesophageal resection in patients with cancer in the oesophagus or gastro-oesophageal junction. We found no overall or progression-free survival advantages by adding radiotherapy, despite better tumour tissue response. Disclosure: All authors have declared no conflicts of interest.